Air pollution control technology handbook. - Schnelle, Karl B., Jr., ....-; Brown, Charles Arnold, 1951- (Boca Raton : CRC, 2002)
In the debate over pollution control, the price of pollution is a key issue. But which is more costly: clean up or prevention? From regulations to technology selection to equipment design, Air Pollution Control Technology Handbook serves as a single source of information on commonly used air pollution control technology. It covers environmental regulations and their history, process design, the cost of air pollution control equipment, and methods of designing equipment for control of gaseous pollutants and particulate matter. This book covers how to:·Review alternative design methods·Select methods for control·Evaluate the costs of control equipment·Examine equipment proposals from vendorsWith its comprehensive coverage of air pollution control processes, the Air Pollution Control Technology Handbook is a detailed reference for the practicing engineer who prepares the basic process engineering and cost estimation required for the design of an air pollution control system. It discusses the topics in depth so that you can apply the methods and equations presented and proceed with equipment design.
Keywords: Luchtvervuiling; Reinigingsinstallaties